Analysis of Department of Elementary School Students' Critical Thinking Abilities through Case Based Learning in the Classroom Action Research Courses - Murniningsih, Murniningsih; Widyawati, Ani; Trisniawati, Trisniawati; Wijayanti, Dian Marta; Effendi, Rubianto (Faculty of Education Universitas Negeri Malang, 2024)
The aim of this research is to describe the results of the analysis of PGSD students' critical thinking abilities in studying the Classroom Action Research course. This research is descriptive qualitative research. The subjects of this research were PGSD students in collaboration classes between lecturers and teacher practitioners in the teaching practitioner program. The collected data is then analyzed using interactions between components systematically between data reduction, data presentation (data display), and Conclusion (conclusion drawing). The results of this research show that PGSD students' critical thinking abilities are throughCase Based Learning increases as shown by the student's ability to formulategap problem while analyzing the root of the problem in learning, offering a relevant literature review, as well as PTK planning that fits the existing model.